PERANCANGAN APLIKASI MANAJEMEN INFORMASI DENGAN MODEL-V BERBASIS WEB PADA HIMPUNAN MAHASISWA SISTEM INFORMASI UNIVERSITAS PAMULANG - Dede Maulana; Risah Subariah (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
The Information Systems Student Association (HMSI) is an information systems student organization of Pamulang University. Since it was ratified by the rector of Pamulang University on March 24, 2021 until now, information management at HMSI UNPAM still uses microsoft office applications for administrative purposes & data storage and uses Instagram & Whatsapp for information dissemination. So it is vulnerable to data loss & ineffective dissemination of information carried out. Research based on these problems is the background for designing a web-based HMSI application that can facilitate organizational management, both administrative and information dissemination. The method of developing the system applied is the V-model. Model-V is a development based on the incorporation of testing in each phase of development through the stages of unit requirements and testing, system design and integration tests, architectural design and system testing, module design and acceptance exams to coding implementation. The advantages of the V-model compared to other development methods are flexibility and ideal time management. For designing this website-based HMSI application, it uses PHP with the Laravel and MySQL frameworks. The result of this study is a website that can facilitate database information management, administration, dissemination of information & student organization agendas.